Kepuasan Nasabah Dilihat dari Faktor Banking Service Quality dan Penggunaan Teknologi Digital dalam Pembukaan Rekening Tabungan Baru - Sudarmadi; Kezia Greatania Galvin (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
This study aims to analyze the impact of Bank Service Quality (BSQ) and digital technology utilization on customer satisfaction at Bank BCA. This research is conducted due to the importance of enhancing service quality and digital technology in the banking industry. The study subjects are customers using new savings account services at the Surakarta branch of Bank BCA, with a sample of 120 randomly selected respondents. Data were collected through a survey questionnaire and analyzed using multiple linear regression. The results indicate that BSQ and digital technology utilization significantly affect customer satisfaction, with an R Square value of 0.956, meaning 95.6% of the variability in customer satisfaction can be explained by these two variables. The t-test shows that both variables have a positive and significant impact on customer satisfaction, both individually and simultaneously. The study's limitations include a sample restricted to a single bank and limited variables, which may not capture all factors influencing customer satisfaction. Future research is advised to expand the scope and variables and to use more diverse research methods. This study recommends improving service quality and digital technology to enhance customer satisfaction.